Constructed Global Space, Constructed Citizenship - Lee, Micky (Javnost-The Public, 2009)
This article examines the relation between global space and citizenship by examining the cases of WTO meeting and Hong Kong Disneyland. Scholars assert that global space can unsettle naturalised social relations. Yet, an ambiguous and vague sense of citizenship and a neoliberal spatiotemporal frame constrain how the state, the media, and the locals interpret the meanings of space, and how citizenship is manifested in space. In the global space of the WTO meeting and the Hong Kong Disneyland, the Hong Kong Chinese identity is reinforced by demonising South Korean farmers and mainland Chinese.